Long-term N inputs shape microbial communities more strongly than current-year inputs in soils under 10-year continuous corn cropping. (September 2021) - Tosi, Micaela; Deen, William; Drijber, Rhae; McPherson, Morgan; Stengel, Ashley; Dunfield, Kari
Abstract: Nitrogen (N) fertilization in agroecosystems can alter soil physicochemical and biological properties. Yet, little is known about the relative importance of short- and long-term effects of N inputs on soil microbial communities. In a continuous corn ( Zea mays L.) trial from southern Ontario, Canada, we analyzed the response of soil microbial community structure to contrasting mineral N fertilization rates applied either continuously for 10 years (low: 30, mid: 87, high: 218 kg N ha −1 y −1 ) or 'shocked' with a higher/lower N rate once every five years. Soil samples (0–15 cm) were collected on the last year of trial at corn early reproductive stage. Microbial biomass was analyzed using fatty acid methyl esters and microbial diversity and community composition using high-throughput sequencing. The effects of N inputs on soil microbial community structure were minor, mostly in the long-term, and slightly different between prokaryotes and fungi. The total N input over 10 years (long-term) was correlated positively with bacterial biomass and negatively with fungal richness. Total N inputs also caused minor shifts in microbial community composition. Shock N rates (short-term) did not affect microbial community structure except for the relative abundance of some taxa. Taxonomic changes were observed at lower levels (i.e., genus), with no clear changes at the phylum level, and low N generally favoured more phylogenetically diverse taxa than high N. Overall, our results suggest that, even under the uniform conditions of corn monoculture, soil microbial communities can be shaped by N fertilization rates commonly used in agriculture. Depending on the functional traits of the sensitive organisms, such structural changes could lead to changes in nutrient cycling dynamics and crop growth. Highlights: Long-term N fertilization rates of corn crops affected soil microbial structure. Total N input over 10 years caused minor shifts in microbial community composition. Bacterial biomass increased and fungal richness decreased with higher total N input. Except for some taxonomic changes, no clear short-term N input effects were detected. Taxonomic changes were mostly observed at genus but not phylum level.